Agitator - July 19, 1900 - (:unkn) unknown (My University, 1900)
Microfilm provided by the Panhandle-Plains Historical Museum and Clarendon ISD.
The Agitator was a newspaper dedicated to making Clarendon and Donley County dry by focusing on prohibition issues across the United States.
Keywords: Agitator; Clarendon (Tex.)--Newspapers.; Donley County (Tex.)--Newspapers.